Peran dan Implementasi DPR Sebagai Bentuk Checks and Balances Terhadap Kebijakan Kepala Otorita IKN - Aziz, Mohammad Rifqi (Jurnal Konstitusi & Demokrasi, 2023)
The 1945 Indonesian Constitution details that regional governments are organized into Provinces, Districts, and Cities, each led by directly elected Governors, Regents, and Mayors. These regions also have a Regional People’s Representative Council (DPRD) to represent citizens and help create local laws with the regional heads. However, in 2022, Indonesia planned to move its capital, introducing a unique regional government setup not outlined in the Constitution. Under Law No. 3 of 2022, the new capital, called Nusantara, will have a special government run by an Authority Body at the ministerial level, headed by a President-appointed leader, not elected by the public. This setup differs significantly because Nusantara won't have a DPRD, leading to questions about how it will maintain checks and balances. This study uses legal analysis to explore these issues, highlighting the important role of the national DPR in ensuring governance principles are upheld in the new capital.